Economic growth and regional income distribution in Semarang district in 1999-2003 - Dani Yus Wijayanto (Indonesia Accounting Research Journal, 2022)
This study aims, To determine the development of the GRDP structure in each sector in Semarang Regency from 1999-2003, To find out the factors inhibiting and supporting the development of the agricultural sector and the industrial sector in Semarang Regency, To find out the distribution of income distribution in Semarang Regency by including the industrial sector and without the industrial sector. This type of research data is using secondary data and primary data. There are two variables studied in this study, namely: Economic growth, and regional income distribution in Semarang Regency in 1999-2003. The technique in collecting data used in this study is the documentation method. The main data used is secondary data based on time series data. The results showed that the development of the PDRB structure of Semarang Regency in 1999-2003 was dominated by four sectors, two of which were the most potential sectors, namely the industrial and services sectors. Based on the LQ method, the industrial sector, the electricity sector, the financial institution sector and the services sector are sectors that have the potential to be developed. Meanwhile, based on the shift share analysis method, the services sector, the construction sector, the electricity sector and the agricultural sector are sectors that are growing faster than the same sector in Central Java province, because their contribution is positive. While the GRDP growth in Semarang Regency is negative, this means that the GRDP growth is slower than the GRDP growth in Central Java Province.